1992
DOI: 10.1152/ajpendo.1992.262.4.e497
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin and cAMP modulation of IGE binding protein production in ovarian granulosa cells

Abstract: Porcine granulosa cells (GC) produce insulin-like growth factor (IGF) binding protein (BP)-3 and IGFBP-2 in culture. A gonadotropin, follicle-stimulating hormone (FSH), dramatically inhibited GC production of these IGFBPs in control cultures and in cultures stimulated by insulin plus epidermal growth factor (EGF) or IGF-I plus EGF. Stimulators of adenylate cyclase (forskolin, cholera toxin) and a derivative of adenosine 3',5'-cyclic monophosphate (cAMP), 8-bromoadenosine 3',5'-cyclic monophosphate, inhibited I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
22
2
Order By: Relevance
“…On the other hand, IGFBP-3 mRNA was found to be preferentially expressed in thecal cells [13], which agrees with our finding of predominant expression in small luteal cells in the current study. However, these data contrast with our in vitro observations [28][29][30][31], which indicate that porcine granulosa cells can secrete IGFBP-3 under some circumstances. Irrespective of the cell type involved, the present observations illustrate dramatic shifts in the type and amount of the IGFBP produced during luteinization.…”
Section: Igf-i Versus Igfbp-3 Mrna (Small and Large Cells)contrasting
confidence: 99%
“…On the other hand, IGFBP-3 mRNA was found to be preferentially expressed in thecal cells [13], which agrees with our finding of predominant expression in small luteal cells in the current study. However, these data contrast with our in vitro observations [28][29][30][31], which indicate that porcine granulosa cells can secrete IGFBP-3 under some circumstances. Irrespective of the cell type involved, the present observations illustrate dramatic shifts in the type and amount of the IGFBP produced during luteinization.…”
Section: Igf-i Versus Igfbp-3 Mrna (Small and Large Cells)contrasting
confidence: 99%
“…Evaluation of the IGFBP profile in control and ACTH-treated gilts confirmed the presence of IGFBP-3 and IGFBP-2 in the FF of individual follicles. Both of these proteins have previously been detected in porcine FF and are known products of granulosa and luteal cells (Howard & Ford 1992, Grimes et al 1994. IGFBP-4 and -5 have also been measured in porcine FF, but were not detected in the current study, indicating that their concentrations are too low (in individual follicles) to be discerned with this method.…”
Section: Figurecontrasting
confidence: 55%
“…Using our method, we cannot exclude that a minor population of IGF-I binding in thecal cells and in apoptotic granulosa cells was due to specific receptors. Concerning IGFBPs in swine ovaries, the expression of IGFBP-2 and -4 mRNAs has been reported in granulosa and thecal cells throughout the follicular development (Zhou et al 1996), and the presence of IGFBP-2, -3 and -4 has been demonstrated in follicular fluid, IGFBP-2 being most related to atresia and IGFBP-3 to preovulatory maturation (Mondschein et al 1991, Grimes et al 1994.…”
Section: Discussionmentioning
confidence: 99%